P193 Non-invasive ventilation: making changes and demonstrating improvement using quality improvement methodology. (December 2018) - Mummery, V; Adeleke, Y; Lin, F; Matthew, D; Woodcock, T; Ritchie, L; McNicholas, C; Bloch, S
Abstract : Introduction and objectives: The BTS audit and NCEPOD report on Non-Invasive Ventilation (NIV) demonstrate significant failings in the care of acute NIV patients. NIV has the potential to reduce mortality by 50% when delivered appropriately, but can do significant harm if poorly managed. Quality improvement (QI) is a relatively new and rapidly increasing discipline in the clinical field. Demonstrating that changes result in improvement can be difficult. However, when improvement can be robustly shown, the data are powerful and can help to ensure stakeholder engagement and continued motivation. As part of a NIHR CLAHRC Northwest London funded QI initiative (April 2017-March 2018), aiming to improve care for acute NIV patients, we used QI methodology and a patient centred approach to develop an NIV bundle, algorithm, standardise training and develop a competency framework. We aimed to demonstrate that these interventions resulted in improved care by using a 'measures for improvement' approach. Method: An Action-Effect Diagram was developed to identify and articulate the aims of the project and how they might be achieved. Stakeholder engagement, process mapping and iterative PDSA cycles to test change were some of the QI methods used. A measurement plan defined our process, outcome and balancing measures. Data were collected prospectively, analysed using Statistical Process Control (SPC) charts and used to inform decision-making, reporting on a fortnightly basis. Results: Since implementation (July 2017), 111 NIV care-bundles have been completed from a possible 185. 535 staff were trained using the updated education framework. SPC charts demonstrated improvements in care, for example in the documentation of NIV parameters (figure 1) we also began to see improvement in the percentage of patients receiving all five points on our COPD treatment algorithm (controlled oxygen, steroids, nebulisers, antibiotics and chest xray prior to NIV), and patients having a ceiling of care discussion prior to NIV. Conclusions: We have demonstrated that by using a robust QI approach, approaching improvement in an evidence-based, systematic and patient centred way we were able to make improvements. Future challenges include efficiently sustaining these improvements to ensure that the new BTS quality standards are met.